A HISTOLOGICAL STUDY OF THE OPTIC TECTUM OF PRISTOLEPIS MALABARICUS (GUNTHER) (PERCIFORMES, TELEOSTEI) - ANAND, SHERLY P.; JOHN, K C (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
The optic tectum of Pristolepis malabaricus is laminated like the general teleostean pattern. Areas associated with the primary sensory function like vision is significantly related to the differences in the feeding habits. P. malabaricus is a carnivore, which feeds upon motile prey like shrimps and small fishes and hence is characterized by a well-developed optic tectum.